Pembuatan Indeks Beranotasi Skripsi Jurusan Manajemen Tahun 2011-2017 di Perpustakaan AKBP-STIE â€œKBPâ€ Padang - Ayunisa, Ghaniya; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractÂ This paper discusses the process of index indexing by annotating thesis of the management in the AKBP-STIE "KBP" Padang library. The purpose of this research is to present or describe how the process of indexing is done by annotating the thesis of the management in the AKBP-STIE "KBP" Padang library. The method used is descriptive method which is described as is. Data was collected by direct observation and asked several questions to librarians in the AKBP-STIE "KBP" library in Padang. The process of making an annotated index is (a) the collection and grouping of management theses in accordance with each management thesis year, after the collection is done, the number of management theses from 2011-2017 is 258 copies; (b) create a management thesis description consisting of the author's name, thesis title, and thesis year; (c) the creation of an management thesis annotation that aims to provide a brief overview of the contents of the management thesis; (d) determination of keywords that aim to simplify and accelerate the retrieval of management theses; (e) Preparation and Media Index of Management Thesis, the media provisions of this annotated index linking are in the form of a book with systematic preparation based on the author's thesis name; (f) Typing an Annotated Index, with the provisions of the arrangement starting from the index, annotations, keywords, and shelf locations as well as the thesis code that has been given by the librarian.Keyword:Â  index with annotation, management scription.